Higher Aortic Stiffness Is Related to Lower Cerebral Blood Flow and Preserved Cerebrovascular Reactivity in Older Adults. Issue 18 (30th October 2018) - Jefferson, Angela L.; Cambronero, Francis E.; Liu, Dandan; Moore, Elizabeth E.; Neal, Jacquelyn E.; Terry, James G.; Nair, Sangeeta; Pechman, Kimberly R.; Rane, Swati; Davis, L. Taylor; Gifford, Katherine A.; Hohman, Timothy J.; et al.
Abstract : Background: Mechanisms underlying the association between age-related arterial stiffening and poor brain health remain elusive. Cerebral blood flow (CBF) homeostasis may be implicated. This study evaluates how aortic stiffening relates to resting CBF and cerebrovascular reactivity (CVR) in older adults. Methods: Vanderbilt Memory & Aging Project participants free of clinical dementia, stroke, and heart failure were studied, including older adults with normal cognition (n=155; age, 72±7 years; 59% male) or mild cognitive impairment (n=115; age, 73±7 years; 57% male). Aortic pulse wave velocity (PWV; meters per second) was quantified from cardiac magnetic resonance. Resting CBF (milliliters per 100 g per minute) and CVR (CBF response to hypercapnic normoxia stimulus) were quantified from pseudocontinuous arterial spin labeling magnetic resonance imaging. Linear regression models related aortic PWV to regional CBF, adjusting for age, race/ethnicity, education, Framingham Stroke Risk Profile (diabetes mellitus, smoking, left ventricular hypertrophy, prevalent cardiovascular disease, atrial fibrillation), hypertension, body mass index, apolipoprotein E4 ( APOE ε4) status, and regional tissue volume. Models were repeated testing PWV× APOE ε4 interactions. Sensitivity analyses excluded participants with prevalent cardiovascular disease and atrial fibrillation. Results: Among participants with normal cognition, higher aortic PWV related to lower frontal lobe CBF (β=−0.43; P =0.04) and higher CVR in the whole brain (β=0.11; P =0.02), frontal lobes (β=0.12; P <0.05), temporal lobes (β=0.11; P =0.02), and occipital lobes (β=0.14; P =0.01). Among APOE ε4 carriers with normal cognition, findings were more pronounced with higher PWV relating to lower whole-brain CBF (β=−1.16; P =0.047), lower temporal lobe CBF (β=−1.81; P =0.004), and higher temporal lobe CVR (β=0.26; P =0.08), although the last result did not meet the a priori significance threshold. Results were similar in sensitivity models. Among participants with mild cognitive impairment, higher aortic PWV related to lower CBF in the occipital lobe (β=−0.70; P =0.02), but this finding was attenuated when participants with prevalent cardiovascular disease and atrial fibrillation were excluded. Among APOE ε4 carriers with mild cognitive impairment, findings were more pronounced with higher PWV relating to lower temporal lobe CBF (β=−1.20; P =0.02). Conclusions: Greater aortic stiffening relates to lower regional CBF and higher CVR in cognitively normal older adults, especially among individuals with increased genetic predisposition for Alzheimer's disease. Central arterial stiffening may contribute to reductions in regional CBF despite preserved cerebrovascular reserve capacity. Abstract : Supplemental Digital Content is available in the text.